2017
DOI: 10.1007/s11356-017-9360-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanoparticles in species of aquaculture interest

Abstract: Recently, it was observed that there is an increasing application of nanoparticles (NPs) in aquaculture. Manufacturers are trying to use nano-based tools to remove the barriers about waterborne food, growth, reproduction, and culturing of species, their health, and water treatment in order to increase aquaculture production rates, being the safe-by-design approach still unapplied. We reviewed the applications of NPs in aquaculture evidencing that the way NPs are applied can be very different: some are direclty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(49 citation statements)
references
References 146 publications
0
49
0
Order By: Relevance
“…Moreover, when in the environment, the capacity of nanoparticles to interact with other pollutants may influence their toxicity (Moore et al, 2006;Fabrega et al, 2011). Studies focused on the toxicity of NPs in aquatic environment showed that NPs toxicity depends on their nature, exposure concentration, shape, size, and surface charge (Sun et al 2016; Jastrzębska and Olszyna 2015) as well as on the time of exposure, medium composition, route of particle administration and target species (Khosravi-Katuli et al 2017). Regarding the use of NPs for water decontamination, the available information is very scarce, in particular the one devoted to the possible toxic impacts of remediated water, resulting from incomplete removal of contaminants, prevalence of NPs residues, or other changes in water physicochemical properties induced by the remediation condition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when in the environment, the capacity of nanoparticles to interact with other pollutants may influence their toxicity (Moore et al, 2006;Fabrega et al, 2011). Studies focused on the toxicity of NPs in aquatic environment showed that NPs toxicity depends on their nature, exposure concentration, shape, size, and surface charge (Sun et al 2016; Jastrzębska and Olszyna 2015) as well as on the time of exposure, medium composition, route of particle administration and target species (Khosravi-Katuli et al 2017). Regarding the use of NPs for water decontamination, the available information is very scarce, in particular the one devoted to the possible toxic impacts of remediated water, resulting from incomplete removal of contaminants, prevalence of NPs residues, or other changes in water physicochemical properties induced by the remediation condition.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was observed that there is increasing application of nanoparticles in aquaculture (Khosravi-Katuli et al 2017). Nanoparticles of elements such as selenium, iron, and chitosan added to diet sources may improve fish production.…”
Section: Other Applications In Aquaculture and Marine Industriesmentioning
confidence: 99%
“…When these materials are discharged into waters, they will have the opportunity to interact with different types of biological and physicochemical factors, as a result leading to substantial negative effects to the surroundings with consequences at the ecological unit level [ 156 ]. Several research works have concentrated on the toxicity of graphene-related NMs in the aqueous environment and it was proved that the toxicity of these graphene-based NMs depends on their surface charge, size, shape, exposure concentration, and nature [ 194 ] and also on the target species, route of particle administration, medium composition, and the time of exposure [ 195 ]. A major problem to be considered during the environmental risk valuation of graphene-based nanomaterials in the aqueous system is indicated by their adsorption abilities.…”
Section: Toxicity Of Nanomaterials In the Aqueous Environmentmentioning
confidence: 99%